Health anxiety in stroke survivors: a cross-sectional study on the prevalence of health anxiety in stroke survivors and its impact on quality of life. Issue 1 (2nd January 2023) - Diamond, Peter R.; Dysch, Leon; Daniels, Jo
Abstract: Purpose: To explore the prevalence of health anxiety in stroke survivors and its relative impact on quality of life. Materials and methods: A cross-sectional design was used including between group comparisons of high and low health anxious stroke survivors. Stroke survivors ( n  = 105) were recruited via online stroke community forums. Participants completed measures of health anxiety (Short Health Anxiety Inventory), general anxiety and depression (Hospital and Anxiety and Depression Scale), disability (WHO Disability Assessment Schedule), and quality of life (Quality of Life Index). Demographics and medical histories were also assessed. Results: Thirty percent of the sample scored above the clinical cut off for health anxiety. Stroke survivors with high health anxiety (HiHA) were found to have significantly lower quality of life ( p  < 0.001) and higher rates of depression ( p  < 0.001). Regression analysis found health anxiety to be a significant predictor of quality of life ( β = –0.12; p  < 0.05) in addition to levels of depression ( β = –0.33; p  < 0.001) and disability ( β = –0.53; p  < 0.001). Conclusions: Almost a third of stroke survivors were experiencing clinical levels of health anxiety, with HiHA significantly associated with lower quality of life. Future research should explore the use of existing evidence based psychological interventions for health anxiety in this population. Implications for rehabilitation: Our findings suggest almost one in three stroke survivors residing in the community have clinical levels of health anxiety. High health anxiety in stroke survivors was significantly related to lower levels of quality of life. Given this finding, evidence-based treatments for health anxiety may improve quality of life and reduce distress for a significant proportion of stroke survivors. Rehabilitation approaches aimed at improving overall quality of life for stroke survivors should consider both physical and psychological interventions, with levels of physical disability, depression and anxiety all significantly associated with quality of life.